Interpersonal Emotional Regulation and Its Relationship to Work Prosperity among Educational Counselors (Journal of the College of Basic Education, 2025)
The current research aims to identify the regulation of interpersonal emotions and thriving at work among educational counselors, in addition to identifying the correlation between them. In order to achieve the research objectives, the researcher adopted the scale of Williams et al. (2018) to identify the regulation of interpersonal emotions and the scale of (Spreitzer et al., 2005) to identify thriving at work, noting that the research boundaries are educational counselors in the six directorates in Baghdad Governorate for the academic year 2024-2025. The research sample included (300) male and female counselors. The data were processed according to the statistical package in the social sciences SPSS. The results showed that educational counselors have regulation of interpersonal emotions and thriving at work, as well as a positive relationship between both variables. The research came out with a set of recommendations and proposals